Cytokine Release Patterns in Mixed Lymphocyte Culture (MLC) of T-Cells with Dendritic Cells (DC) Generated from AML Blasts Contribute to Predict anti-Leukaemic T-Cell Reactions and Patients' Response to Immunotherapy. (2nd November 2015) - Fischbacher, Dorothea; Merle, Marion; Liepert, Anja; Grabrucker, Christine; Kroell, Tanja; Kremser, Andreas; Dreyßig, Julia; Freudenreich, Markus; Schuster, Friedhelm; Borkhardt, Arndt; Kraemer, Doris; Koehne, Claus-Henning; et al.
Abstract: To enlighten interactions between autologous, allogeneic or T-cells from patients after stem cell transplantation with leukaemia-derived-dendritic-cells containing dendritic cells or blast containing mononuclear cells ( n  = 21, respectively), we determined cytokine-concentrations (interleukin 2, 4, 6, 10, tumor-necrosis-factor-α, interferon-γ) in supernatants of mixed-lymphocyte-culture and in serum ( n  = 16) of 20 patients with acute myeloid leukaemia and three patients with myelodysplastic syndromes by cytometric-bead-assay. We correlated our data with lytic capabilities of stimulated T-cells in a fluorolysis-assay and clinical data: Dendritic-cell-/mononuclear-cell-stimulation of T-cells resulted in increased cytokine-levels in culture-medium compared to serum. There were no significant differences between cytokine-patterns of cases with/without lytic T-cell-activity, response to immunotherapy (stem cell transplantation/ donor-lymphocyte-infusion) or graft-versus-host-disease. However, some predictive cytokine-cut-off-values for antileukaemic T-cell-activity, patients' response to immunotherapy and graft-versus-host-disease could be defined. Cytokine-profiles alone, without functional assays, are no useful tool to predict antileukaemic T-cell-function, although they can indicate lytic T-cell-activity, patients' response to immunotherapy and graft-versus-host-disease.